Description of a new species of Stenotabanus from Venezuela (Diptera: Tabanidae) - Gorayeb, Inocêncio de Sousa; Gómez, Zaide Tiape; Rios, Mercedes Velásquez de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Stenotabanus (Stenotabanus) clavijoi n.sp. is described based on two females collected in the states of Aragua and Tachira, Venezuela. This is the 59th species of the subgenus Stenotabanus and the third from Venezuela. Diagnostic characters are: large species in relation to other species of the subgenus; dorsum of the body dark brown to black and belly with pruinescence and clear setae; frons with inflated callus, square, dark brown to black, shiny with an upper extension; hyaline wings; yellowish brown legs; abdomen with posterior margin with pruinescence and white hair with the aspect of narrow bands; cerci dorsally visible.